Clinical Characteristics of Necrotizing Enterocolitis in Preterm Patients With and Without Persistent Ductus Arteriosus and in Patients With Congenital Heart Disease - Diez, Sonja; Tielesch, Lea; Weiss, Christel; Halbfass, Julia; Müller, Hanna; Besendörfer, Manuel (Frontiers in Pediatrics, 2020)
Background: Diagnosis and management of NEC is based on clinical, radiological and laboratory findings. Discrimination of pathogens for an improved understanding of NEC in preterm infants and NEC in infants with congenital heart disease has been previously discussed and enables evaluation of further NEC biomarkers. Patients and Methods: Within a study period of 11 years (2008-2019), we identified 107 patients with diagnosis of NEC at our primary care center. 36 out of 54 patients suffering from NEC in high Bell stages who underwent surgery met inclusion criteria. These patients were classified according to their cardiac status and analyses of clinical factors influencing NEC were conducted. Additionally, clinical factors associated with a fulminant course of NEC were examined. Univariable and multivariable analyses were performed. Results: The study populations consisted of 12 preterm infants with NEC but without patent ductus arteriosus (PT-NEC), 7 preterm infants with NEC and patent ductus arteriosus (PDA-NEC) and 17 infants with NEC and congenital heart disease (CHD-NEC). Blood flow in intestinal vessels was impaired in infants with PDA-NEC and CDH-NEC. Therefore, we used logistic regression to compare PDA-NEC and CDH-NEC infants with PT-NEC infants: positive bacterial culture of intraoperative swabs (p=0.0199; odds ratio: 21.9) and macroscopic intestinal necrosis (p=0.0033; odds ratio: 43.5) were observed more frequently in the first group. Furthermore, multiple regression analysis determined the NEC localization (p=0.0243) as significant factor correlated with a fulminant course. Compared to a NEC exclusively localized in the colon, there is a 5.8- fold increased risk of a fulminant course when small intestine is affected and a 42-fold increase when both, small intestine and colon, were affected. Conclusion: An early diagnosis and timely surgical intervention of NEC, especially in infants with PDA and CDH may be considered to avoid major bowel necrosis (resulting in loss of intestinal tissue) and multiple operations.